The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1136/bmj-2021-067475
|View full text |Cite
|
Sign up to set email alerts
|

Evidence on acupuncture therapies is underused in clinical practice and health policy

Abstract: Nenggui Xu and colleagues call for more effective evidence dissemination of and research into promising acupuncture therapies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 28 publications
(81 reference statements)
1
74
0
Order By: Relevance
“…The main time is 30 min (31.71%) (Feng et al, 2013 ; Tian et al, 2015 ; Han et al, 2017 ; Jiang et al, 2017 ; Lin et al, 2017 ; Liu et al, 2017 ; He et al, 2018 ; Yang et al, 2019 ; Gao et al, 2020 ; Wang Z. et al, 2020 ; Wang H. L. et al, 2021 ; Bu et al, 2022 ; Chen et al, 2022 ), 20 min (21.95%) (Wang et al, 2004 ; Li and Lai, 2007 ; Lin and Wang, 2008 ; Shao et al, 2008 ; Wei et al, 2011 ; Zhu et al, 2012 , 2013 ; Zhang et al, 2017 ; Su et al, 2019 ), 30 S (21.95%) (Zhao et al, 2011 ; Zhang et al, 2014 ; Li et al, 2015 , 2016 ; Ye et al, 2017b ; Du et al, 2018 ; Yang et al, 2018b ; Pan et al, 2021 ; Xu and Zhang, 2022 ) and 10 min (17.07%) (Niu et al, 2009 ; Zhu et al, 2018 ; Wang L. et al, 2020 ; Yang et al, 2020 ; Zheng et al, 2020 ; Cao et al, 2021 ). All literatures indicated the duration of the entire treatment course, namely 14 days (42.86%) (Li et al, 2015 , 2016 ; Wang et al, 2015 ; Ye et al, 2017b ; Du et al, 2018 ; Yang et al, 2018b , 2019 , 2020 ; Zhu et al, 2018 ; Gao et al, 2020 ; Guo et al, 2020 ; Ma et al, 2020 ; Wang L. et al, 2020 ; Wang Z. et al, 2020 ; Zheng et al, 2020 ; Cao et al, 2021 ; Pan et al, 2021 ; Lu et al, 2022 ), 15 days (11.90%) (Wang et al, 2004 ; Li and Lai,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main time is 30 min (31.71%) (Feng et al, 2013 ; Tian et al, 2015 ; Han et al, 2017 ; Jiang et al, 2017 ; Lin et al, 2017 ; Liu et al, 2017 ; He et al, 2018 ; Yang et al, 2019 ; Gao et al, 2020 ; Wang Z. et al, 2020 ; Wang H. L. et al, 2021 ; Bu et al, 2022 ; Chen et al, 2022 ), 20 min (21.95%) (Wang et al, 2004 ; Li and Lai, 2007 ; Lin and Wang, 2008 ; Shao et al, 2008 ; Wei et al, 2011 ; Zhu et al, 2012 , 2013 ; Zhang et al, 2017 ; Su et al, 2019 ), 30 S (21.95%) (Zhao et al, 2011 ; Zhang et al, 2014 ; Li et al, 2015 , 2016 ; Ye et al, 2017b ; Du et al, 2018 ; Yang et al, 2018b ; Pan et al, 2021 ; Xu and Zhang, 2022 ) and 10 min (17.07%) (Niu et al, 2009 ; Zhu et al, 2018 ; Wang L. et al, 2020 ; Yang et al, 2020 ; Zheng et al, 2020 ; Cao et al, 2021 ). All literatures indicated the duration of the entire treatment course, namely 14 days (42.86%) (Li et al, 2015 , 2016 ; Wang et al, 2015 ; Ye et al, 2017b ; Du et al, 2018 ; Yang et al, 2018b , 2019 , 2020 ; Zhu et al, 2018 ; Gao et al, 2020 ; Guo et al, 2020 ; Ma et al, 2020 ; Wang L. et al, 2020 ; Wang Z. et al, 2020 ; Zheng et al, 2020 ; Cao et al, 2021 ; Pan et al, 2021 ; Lu et al, 2022 ), 15 days (11.90%) (Wang et al, 2004 ; Li and Lai,…”
Section: Resultsmentioning
confidence: 99%
“…Acupuncture is the most widely used traditional and complementary medicine, it was used in 113 countries worldwide, and was commonly performed to treat disorders of the motor, nervous, digestive, endocrine, and reproductive systems (Zhang et al, 2022 ). Recent studies have found that acupuncture showed very clear efficacy in the treatment of VD (Lu et al, 2022 ). With the deepening of animal studies, a large amount of evidences showed that acupuncture can effectively treat cognitive dysfunction in animals through multiple targets or pathways (Ye et al, 2017a ).…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, our case shows that acupuncture eliminated the symptoms of weakness and numbness and pain in ICI-related GBS patient's limbs and improved their quality of life. Recent research shows that acupuncture has advantages in treating neurological disorders ( 49 ). Based on our experience, we believe that acupuncture may be an effective, economical, and safe complementary therapy for treating GBS.…”
Section: Discussionmentioning
confidence: 99%
“…The adverse events related to acupuncture are usually mild, and most of them can be avoided through standardizing clinical practices [ 22 , 23 ]. With the rapidly growing research on the clinical application of acupuncture, the evidence of acupuncture's therapeutic effects on neurological disease has increased [ 24 ]. Clinical studies have proved the superior effects of acupuncture on ameliorating vertigo severity and improving the vertebrobasilar blood flow velocity in PCIV patients [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%